Characterization of the ERβ(–)/–mouse heart - Förster, Carola (National Academy of Sciences, 2004)
Although the heart responds to estrogen, it is not clear whether estrogen acts directly on heart muscle or indirectly by means of the vascular, immune, or nervous system. No role for estrogen receptor (ER) β in the heart has been established, but ERβ(–/–) mice are hypertensive, and as they age, their hearts become enlarged. Histological and ultrastructural analysis of the heart revealed a disarray of myocytes, a disruption of intercalated discs, an increase in the number and size of gap junctions, and a profound alteration in nuclear structure, concomitantly with a loss of expression of lamin A/C from the nuclear envelope. In the lungs of ERβ(–/–) mice, lamin A/C was located in the nuclear membrane, indicating that lamin A/C is not an ERβ-regulated gene. Immunohistochemical studies with ERβ antibodies failed to detect ERβ in the myocardium. We conclude that abnormalities in heart morphology in ERβ(–/–) mice are likely due to stress on the nuclear envelope as a result of the chronic sustained systolic and diastolic hypertension observed in ERβ(–/–) mice. Because neither ERα nor ERβ could be detected in heart muscle, the effects of estrogen on the myocardium seem to be indirect.